Rewiring: Cross-Business-Unit Collaborations in Multibusiness Organizations - Martin, Jeffrey A.; Eisenhardt, Kathleen M. (Academy of Management Journal, 2010)
Cross-business-unit collaboration is central to large firms' value creation, yet empirical support for the prevailing view that a corporate process best fosters such collaboration has been unconvincing. This study of six firms asks how executives create collaborations that perform at high levels. Our emergent theory unexpectedly emphasizes that a BU-centric process led by “multibusiness teams” of general managers leads to better collaborations than a corporate-centric process. We contribute to concepts in information processing, transaction cost economics, and social network theories. Our most fundamental insight extends complexity theory: we find that multibusiness organizations with strong performance operate as complex adaptive systems.